Data on Microclimate in hollow trees and how it affects an inhabiting beetle species, Osmoderma eremita - Data om mikroklimat i ihåliga träd och hur det påverkar ett boende skalbaggar, Osmoderma eremita - Lindman, Ly (Swedish University of Agricultural Sciences, 2022)
The data includes measured habitat characteristics, microclimatic variables, and species data collected with mark-recapture method. It was used for analyses to explore microclimate in tree hollows in relation to tree characteristics; and how these variables affect the occurrence and body size of Osmoderma eremita (hermit beetle). Manuscript: "Microclimate in hollow trees and how it affects an inhabiting beetle species, Osmoderma eremita". The study is in English.

Species-related data is collected with mark-recapture method (pitfall trap).
Moisture/humidity is measured with soil moisture meter (GS3 sensor; Decagon Devices).
Temperature data is recorded with Lascar EL-USB-1 data-loggers.

OE_MC_publish_ambient.tsv: 9766 R × 9 C
OE_MC_publish_internal.tsv: 9766 R × 55 C
OE_MC_publish_R.tsv: 47 R × 67 C
OE_MC_publish_RH.tsv: 53 R × 31 C

Specimens_data_publish_b_length-habitat-MC.tsv: 256 R × 24 C
Specimens_data_publish_Recapture.tsv: 500 R × 6 C

Data inkluderar uppmätta habitategenskaper, mikroklimatiska variabler och artdata som samlats in med mark-återfångstmetoden. Den användes för analyser för att utforska mikroklimat i trädgropar i relation till trädets egenskaper; och hur dessa variabler påverkar förekomsten och kroppsstorleken av Osmoderma eremita (läderbagge). Manuskript: "Mikroklimat i ihåliga träd och hur det påverkar en levande skalbaggarart, Osmoderma eremita". Studien är på engelska.

Species-related data is collected with mark-recapture method (pitfall trap).
Moisture/humidity is measured with soil moisture meter (GS3 sensor; Decagon Devices).
Temperature data is recorded with Lascar EL-USB-1 data-loggers.

OE_MC_publish_ambient.tsv: 9766 R × 9 C
OE_MC_publish_internal.tsv: 9766 R × 55 C
OE_MC_publish_R.tsv: 47 R × 67 C
OE_MC_publish_RH.tsv: 53 R × 31 C

Specimens_data_publish_b_length-habitat-MC.tsv: 256 R × 24 C
Specimens_data_publish_Recapture.tsv: 500 R × 6 C
Data om mikroklimat i ihåliga träd och hur det påverkar ett boende skalbaggar, Osmoderma eremita - Data on Microclimate in hollow trees and how it affects an inhabiting beetle species, Osmoderma eremita
Microclimate in hollow trees and how it affects an inhabiting beetle species, Osmoderma eremita
Keywords: microclimate; mikroklimat; hermit beetle; läderbagge; Ecology; Ekologi